Anomalous drainage of isolated superior caval vein to the left atrium: the oldest reported unrepaired case. (15th February 2017) - Boutsikou, Maria; Pennell, Dudley J.; Nyktari, Eva
Abstract: Isolated right superior caval vein drainage into the left atrium is a rare congenital cardiac anomaly usually presenting with hypoxaemia and cyanosis. Surgical repair is the definitive treatment for this condition. In this report, we present the case of a 72-year-old patient with uncorrected anomalous drainage of a right superior caval vein into the left atrium, first diagnosed in the 1960s. To the best of our knowledge, this is the oldest reported unrepaired case.